Технологии развития навыков поликультурного взаимодействия в образовательной среде - Богачева, Татьяна Юрьевна (Զանգակ հրատ.)
Հոդվածում արծարծված է միջմշակութային փոխգործունեության խնդիրը: Միջմշակութային միջավայրում գտնվող իրավիճակներում միջմշակութային փոխգործունեության խնդրի ուսումնասիրությունների հիման վրա փորձարկվել են միջմշակութային փոխգործունեության հմտությունների զարգացման տարբեր տեխնոլոգիաներ: Հոդվածում նկարագրված են առավել արդյունավետ տեխնոլոգիաներ: The article is dedicated to the problem of multicultural education. On the basis of studying the problems of interpersonal interaction the author develops the ability to apply effective intercultural dialogue, gives a characterization of this process. Specific technology development of skills multicultural student interaction in situation of entering in the multicultural environment is developed in the article.
Keywords: Культура